Pilot evaluation of home delivery programme in haemophilia. - Megías‐Vericat, J. E.; Monte‐Boquet, E.; Martín‐Cerezuela, M.; Cuéllar‐Monreal, M. J.; Tarazona‐Casany, M. V.; Pérez‐Huertas, P.; Bonanad, S.; Poveda‐Andrés, J. L. (Journal of Clinical Pharmacy & Therapeutics, 2018)
Summary: What is known and objectives: Most of the clotting factor (CF) dispensations to haemophiliac patients are centralized in a few haemophilia treatment centres, necessitating frequent visits and long travel distances. The aim was to evaluate the home delivery programme developed by the Outpatient Pharmaceutical Care Unit (OPCU) through the association of patients (ASHECOVA). Methods: A specific software programme was designed to communicate the individual CF requirements. Dispensations were prepared in advance, and an ASHECOVA member collected and delivered to patients' homes in optimal conditions. Data regarding the programme were analysed from December 2011 to December 2017. An electronic satisfaction survey with 34 questions was conducted, asking about organizational aspects, education and communication, use of apps and satisfaction level. Results and discussion: Forty‐nine patients were included and 2464 home deliveries were made, without any reported incident related to dispensation errors, drug preservation, communication or confidentiality problems. This system avoids 11.4 annual dispensation visits per patient to OCPU, and a mean travel distance, time and cost of 1189.1 km, 945.3 minutes and 373.5 euros, respectively. Overall satisfaction with home delivery was 9.7, without any change suggested in the current system. Ninety‐five per cent of individuals believed that the programme improves adherence and all patients would recommend it to other patients. The most common benefits reported were less frequent visits to hospital, reducing time and cost spent on transportation. What is new and conclusion: The home delivery programme guarantees a proper follow‐up of treatments with full patient satisfaction. This programme allows OPCU to achieve better pharmaceutical care, traceability of the process and optimization of working times and CF stock management. The home delivery process include: 1) Patient authorizes individually a delegated dispensation; 2) On‐line communication Pharmacy and Patients' Association; 3) Pharmaceutical validation and dispensation is prepared in advance; 4) Patients' Association collects the medication and delivers it to patient´s home in optimal conditions.